Ecological sustainability and environmental risks of agricultural intensification in inland valleys in Benin - Djagba, J.F.; Zwart, Sander J.; Houssou, C.S.; Tenté, B.H.A.; Kiepe, P. (Springer, 2019)
To meet food demand after the failure of irrigation system developments, agricultural intensification is occurring in inland valley agro-ecosystems in sub-Saharan Africa. Agricultural enhancement in inland valleys, which undermines environmental sustainability, was assessed using 'Driving Force–Pressure–State–Impact–Response' approach in four agro-ecological zones of Benin. The survey revealed that inland valleys are largely devoid of ligneous species. Crop residues are mainly transferred from inland valley fields to feed cattle, burnt in situ by the farmers themselves or abandoned to wildfires or to pasture—not mulched. Crop diversification is not universal and is limited to rice and vegetables crops. Monocropping of rice, practised by 83.3% of inland valley farmers, requires large chemical fertilizer application despite their impacts on environment including land degradation and water contamination. A major challenge is to determine means of characterizing entire agro-ecosystems of inland valleys in a way that is simple enough to be effectively and efficiently monitored. Inland valley agricultural development projects might include backstopping activities and policies that enable monitoring of chemical inputs and farming practices in inland valleys to reduce negative impacts on the environment and human health.